Answer:
D’(-1,-2)
Step-by-step explanation:
Left = x -2 = 1-2 = -1
down = y-5 = 3-5 = -2
I hope my answer is correct
I think, the answer will be -7
We have:
f(x)=1/(x-2)
g(x)
Then:
(fg)(x)=[1/(x-2)](g(x))=g(x)/(x-2)
Now; we calculate: (fg)`(x)
Remember: (u/v)=(u`v-vu´)/v²
Therefore:
(fg)´(x)=[g´(x)*(x-2) - 1*g(x)]/ (x-2)²
We know that:
g´(1)=-1
(fg)´(1)=6
Therefore:
6=[-1*(1-2)-g(1)]/(1-2)²
6=[1-g(1)]/1
6=1-g(1)
-g(1)=6-1
g(1)=-5
Answer: B. -5
Answer:
hiii
Step-by-step explanation:
1. Multiply both sides by 3
38/3x x 3 +16/3. x =-20x3
2. Simplfy
38x+16=-60
3. Subtract 16 from both sides
38x+16-16=-60-16
4. Simplfy
38x=-76
5. Divide both sides by 38
38x/38=-76/38
6. Simplfy
x=-2
Is there a graph ? But I’m thinking z>1